Financing Restructuring During the Covid-19 Pandemic: The Tadhbiq Ahkam Paradigm - Endah Robiatul Adawiyah; Rudi Setiadi; Dadang Rohandi; Udin Wahrudin; Inayatul Ummah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: The Paper is to study the Restukturization Of Financing During The Covid-19 Pandemic: Maqashid Paradigm As-Syar'iyahDesign/Method/Approach : This research uses qualitative methods with a library study approach. in analyzing the position of financing restucturization during the pandemic from the point of view of maqasid al-syar'iyahFindings: The discussion is considered important because by digging from the point of view of muamalah figh in terms of Magashid Syari’ah so that the discussion specifically becomes the first two discussions, from the restructuring process of financing during the pandemic, restructuring which was developed with the istimbat ahkam with the aim of magashid syari’ah as part of Hifdul Maal [Maintaining Property] which is motivated by the social condition of public health, namely during the pandemic period empirically with analysis and argumentation, the second is the harmonization of syari’ah policies with the situation. Research subject related to causes and reasons for implementing decisions on financing restricting with Magashid Syari’ah., a paradigm developed through financing risk mitigation and the Magashid As-Syari’ah paradigm in legal protection based on the existence of benefits that are dharuriyyat [primary needs]. Hajiyat [secondary needs], and Tahsinivat [tertiary needs], with regard to protection of proferty [hifdz a-Maal] and hifdz al –nafs [guarding the soul] with legal arguments built starting from the view that the return on financing is carried out from bank financial institutioins Sharia is an obligation that must be fulfilled, in the process of fulfilling the obligatons given by financial institutions based on general and special considerations, especialty for conditions beyons the will and ability of humans, the ability to return financing is hindered due the covid-19 pandemic, there is a restructuring formulation. A is, namely postponemet of loan principal, postponement of principal and margin, delay of remaining principal extension of repayment period, and reduction in margins on people’s business financing (PUR) Originality/Values: The main contribution of this research is a concern in filling the gap in how the concept of Islamic economics in the restucturization of financing to business actors